2016 International Joint Conference on Neural Networks (IJCNN) 2016
DOI: 10.1109/ijcnn.2016.7727452
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Effective Fronto-Parietal connectivity during Motor Imagery using partial granger causality analysis

Abstract: Connectivity analysis has become an essential tool for the evaluation of functional brain dynamics. The functional connectivity between different parts of the brain, or between different sensors, is assumed to provide key information for the discrimination of brain responses. In this study, we propose an estimation of effective cortical connectivity measures in frontal and parietal areas of human brain during four different Motor Imagery (MI) tasks. Feedback based brain-computer interface (BCI) technology has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
7
13
0
Order By: Relevance
“…Our results show the frontal and parietal brain regions as target areas during 3PP, mainly in β. This is consistent with Rathee et al (2016) who reported that, using the partial Granger causality during the right hand MI, the higher FIGURE 13 | Mean node betweenness centrality for both participants shown in color only at the sensors with an incremental trend in comparison to the other condition. For each frequency band, the heads to the left (A,C,E) show the cases when the node betweenness centrality in 1PP increased in comparison to 3PP, while the heads to the right (B,D,F) show those for which 3PP increased in comparison to 1PP.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show the frontal and parietal brain regions as target areas during 3PP, mainly in β. This is consistent with Rathee et al (2016) who reported that, using the partial Granger causality during the right hand MI, the higher FIGURE 13 | Mean node betweenness centrality for both participants shown in color only at the sensors with an incremental trend in comparison to the other condition. For each frequency band, the heads to the left (A,C,E) show the cases when the node betweenness centrality in 1PP increased in comparison to 3PP, while the heads to the right (B,D,F) show those for which 3PP increased in comparison to 1PP.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5] show that, for left-and right-hand MI tasks, the electrode signals recorded from opposite position function mainly as the causal source while the ipsilateral channel signals operate mostly as the net target almost within the whole 2 s after stimulus. These alpha oscillatory activities at scalp-level are in agreement with the direction of information flow postulated in the MI literatures [5,40].…”
Section: [Rls] [Urols With B-splines] [Ols With B-splines] [Rols Withsupporting
confidence: 90%
“…In the present work, in line with our previous study [23], we estimate the single-trial directed functional connectivity features to elucidate the interaction among the EEG signals during various MI tasks (left hand, right hand, feet, and tongue) and CI tasks (word generation, spatial navigation, and subtraction imagery task). In particular, we implemented time-domain partial granger causality (PGC) [24] along with PDC and DTF on the two publically available datasets.…”
Section: Introductionmentioning
confidence: 84%